2021
DOI: 10.1186/s12903-021-01807-6
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of denture stomatitis in cigarette and hookah smokers and opium addicts: findings from Rafsanjan Cohort Study

Abstract: Background The aim of this study was to investigate the association of denture stomatitis prevalence with cigarette, hookah and opium consumption and also dose–response relationship between the cigarette smoking duration and odds of denture stomatitis in population of Rafsanjan cohort center. Methods This cross-sectional study based on data of Rafsanjan Cohort Study (RCS) with 10,000 participants. After applying inclusion and exclusion criteria, 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…This parameter is essential due to the higher incidence of periodontitis in older individuals and limiting this age range could lead to a scientific error. The study assessing denture prosthesis in its participants 18 reported a mild prevalence of men who were older than participants in other studies.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This parameter is essential due to the higher incidence of periodontitis in older individuals and limiting this age range could lead to a scientific error. The study assessing denture prosthesis in its participants 18 reported a mild prevalence of men who were older than participants in other studies.…”
Section: Discussionmentioning
confidence: 88%
“…Seven studies also compared WS and nonsmokers. [14][15][16][17][18][19][20] Three studies evaluated adult patients from 17-14 or 18- 15,19 to 60-yearsold, while six studies restricted the age range to reduce the risk of age interference on results. [16][17][18][20][21][22] Seven articles rated the Middle Eastern population [14][15][16][17][18][19][20] and two articles North African participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Between 15% and 70% of denture wearers have Candida stomatitis related to their removable prosthesis [ 1 ]. The prevalence of this pathology is preponderant among hospitalized elderly people [ 2 ], smokers [ 3 ], and people with associated affections such as diabetes [ 4 ]. This disease also called “denture-related Candida stomatitis” (DRCS), and is considered an infectious inflammation, different from sterile inflammation, characterized by mechanical denture stress [ 5 ] and an imbalance of the oral microbial flora or dysbiosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%